HUBUNGAN PENGETAHUAN IBU TENTANG ASUPAN PROTEIN DAN TINGKAT KECUKUPAN PROTEIN DENGAN KADAR ALBUMIN SERUM PADA IBU HAMIL (Studi di Kecamatan Bulu Kabupaten Temanggung) - Nova Adiani Priastari; Sri Achadi Nugraheni; Muhammad Zen Rahfiludin (Jurnal Kesehatan Masyarakat (Undip), 2017)
Mother mortality rate is still high and is an important indicator to determine public health degree. The most common cause of mother’s mortaity is pre eclampsia because during pregnancy, albumin level inside the plasm is decreasing. The purpose of this research was to analyze the correlation of mother’s knowledge about protein intake with albumin serum level in pregnant women in Bulu District, Temanggung Regency. This was an observasional quantitative research with cross sectional approach. Samples in this research were 53 pregnant women in second and third trimester. Data was collected using questionnaire and FFQ form and analyzed Rank Spearman and Pearson Product Moment test. The results of this research showed that most of the pregnant women had enough knowledge which were (60,4%), level of protein adequacy was normal which were (90,6%%), and level of albumin serum was normal which were (92,5%). The results showed no correlation of mother’s knowledge and level of protein adequacy with level of albumin serum while there was a correlation of mother’s knowledge with level of protein adequacy. This research suggested pregnant women to increase nutritional intake for the body and the baby also Communication, Information and Education was needed to increase pregnant women’s knowledge.